Unlocking Opportunities: A Practical Examination of Free Online Micro-credentials in Teacher Professionalization - The, Hery Yanto (Jurnal Guru Indonesia, 2023)
AbstractThis study fills this gap by providing a case study that illustrates how to use free online training to obtain useful micro-credentials. Insights from the researcher's participation in free online professional development courses are shared. These courses, which encompass learning design and technology, are in line with the researcher's responsibilities as an instructor of second-language education. This study shows how important it is to find and use high-quality professional development choices that are affordable. The methods used in the study can be used by other educators, which will help them improve in their careers and show that they are committed to lifelong learning. By showing practical steps, this study helps teachers make better decisions, which can lead to job growth and better learning outcomes. Wawasan dari partisipasi peneliti dalam pelatihan pengembangan profesional daring gratis dipaparkan di sini. Pelatihan-pelatihan tersebut, yang mencakup desain dan teknologi pembelajaran, sejalan dengan tanggung jawab peneliti sebagai instruktur pendidikan bahasa kedua. Penelitian ini menunjukkan pentingnya menemukan dan menggunakan pilihan pengembangan profesional berkualitas tinggi. Metode yang digunakan dalam penelitian ini dapat digunakan oleh para pengajar lain, yang akan membantu mereka meningkatkan karier mereka dan menunjukkan bahwa mereka berkomitmen untuk belajar sepanjang hayat. Dengan menunjukkan langkah-langkah praktis, penelitian ini membantu guru membuat keputusan yang lebih baik, yang dapat membawa mereka pada pertumbuhan karier dan hasil pembelajaran yang lebih baik.